Business cycle implications of mortgage spreads - Karl Walentin (Sveriges Riksbank, 2014)
How do aggregate quantities at the business cycle frequency respond to shocks to the spread between residential mortgage rates and government bonds? Using a structural VAR approach, we .nd that mortgage spread shocks impact the real economy by both economically and statistically signi.cant magnitudes: a 100 basis point decline in the spread causes a peak increase in consumption, residential investment and GDP by 1.6 percent, 6.2 percent and 1.9 percent, respectively. These eects are magni.ed when the policy rate is held .xed, as was the case in the US during the recent implementation of unconventional monetary policy.
Keywords: E21; E32; E44; E52; R21; 330; Sources of business cycles; unconventional monetary policy; credit supply; housing demand; house prices; financial frictions